ANALISA PERBANDINGAN RETURN INVESTASI LOGAM MULIA DAN RETURN DEPOSITO DALAM JANGKA WAKTU 2013-2017 - Elok Kurniawati (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2019)
This study is to find out an analysis of the comparison of gold investment returns and deposit returns in the 2013-2018 period. The test in this study uses a t-test or a different test, which will compare the return value of gold investment and investment deposits or deposit interest for the past five years. The sample used data from the Ministry of Finance and listed gold companies and banking data that has been published. The results of the data analysis that has been done, it is known that there is a difference between the risk (risk) of deposit investment with gold. Investment risk is higher than the risk (investment) of gold investment. In addition, there is also a difference between the rate of return on deposits and the rate of return on investment in gold. The rate of return on investment in deposits is higher than the rate of return on gold investment.